Non‐native plant invasion can accelerate global climate change by increasing wetland methane and terrestrial nitrous oxide emissions. (19th June 2022) - Bezabih Beyene, Bahilu; Li, Junjie; Yuan, Junji; Dong, Yanhong; Liu, Deyan; Chen, Zengming; Kim, Jinhyun; Kang, Hojeong; Freeman, Chris; Ding, Weixin
Abstract: Approximately 17% of the land worldwide is considered highly vulnerable to non‐native plant invasion, which can dramatically alter nutrient cycles and influence greenhouse gas (GHG) emissions in terrestrial and wetland ecosystems. However, a systematic investigation of the impact of non‐native plant invasion on GHG dynamics at a global scale has not yet been conducted, making it impossible to predict the exact biological feedback of non‐native plant invasion to global climate change. Here, we compiled 273 paired observational cases from 94 peer‐reviewed articles to evaluate the effects of plant invasion on GHG emissions and to identify the associated key drivers. Non‐native plant invasion significantly increased methane (CH4 ) emissions from 129 kg CH4 ha −1 year −1 in natural wetlands to 217 kg CH4 ha −1 year −1 in invaded wetlands. Plant invasion showed a significant tendency to increase CH4 uptakes from 2.95 to 3.64 kg CH4 ha −1 year −1 in terrestrial ecosystems. Invasive plant species also significantly increased nitrous oxide (N2 O) emissions in grasslands from an average of 0.76 kg N2 O ha −1 year −1 in native sites to 1.35 kg N2 O ha −1 year −1 but did not affect N2 O emissions in forests or wetlands. Soil organic carbon, mean annual air temperature (MAT), and nitrogenous deposition (N_DEP) were the key factors responsible for the changes in wetland CH4 emissions due to plant invasion. The responses of terrestrial CH4 uptake rates to plant invasion were mainly driven by MAT, soil NH4 +, and soil moisture. Soil NO3 −, mean annual precipitation, and N_DEP affected terrestrial N2 O emissions in response to plant invasion. Our meta‐analysis not only sheds light on the stimulatory effects of plant invasion on GHG emissions from wetland and terrestrial ecosystems but also improves our current understanding of the mechanisms underlying the responses of GHG emissions to plant invasion. Abstract : Invasion by non‐native plants is a critical ecological threat, while the situation could be worse because plant invasion can accelerate global climate change by increasing wetland methane and terrestrial nitrous oxide emissions. Based on a summarization of available data, methane emissions in coastal wetlands and nitrous oxide emissions in grasslands were found to increase by 130% and 77.6%, respectively, due to non‐native plants invasion, albeit the 57.0% increase of methane uptakes in invaded grasslands.